Factors Leading to Poor Water Sanitation Hygiene Among Primary School Going Children in Chitungwiza - Dube, Blessing (J Public Health Africa, 2012)
Although the world has progressed in the area of water and sanitation, more than 2.3 billion people still live without access to sanitation facilities and some are unable to practice basic hygiene. Access to water and basic sanitation has deteriorated in Chitungwiza and children are at risk of developing illness and missing school due to the deterioration. We sought to investigate the predisposing, enabling and reinforcing factors that are causally related to water- and sanitation- related hygiene practices among school going children. A random sample of 400 primary school children (196 males, 204 females) in four schools in Chitungwiza town, Zimbabwe was interviewed. Behavioural factors were assessed through cross examination of the PROCEED PRECEDE Model. The respondents had been stratified through the random sampling where strata were classes. A structured observation checklist was also administered to assess hygiene enabling facilities for each school. Children’s knowledge and perceptions were inconsistent with hygienic behaviour. The family institution seemed to play a more important role in life skills training and positive reinforcement compared to the school (50% vs 27.3%). There was no association between a child’s sex, age and parents’ occupation with any of the factors assessed (P=0.646). Schools did not provide a hygiene enabling environment as there were no learning materials, policy and resources on hygiene and health. The challenges lay in the provision of hygiene enabling facilities, particularly, the lack of access to sanitation for the maturing girl child and a school curriculum that provides positive reinforcement and practical life skills training approach.